Correction: High-resolution DNA size enrichment using a magnetic nano-platform and application in non-invasive prenatal testing. Issue 3 (6th January 2022) - Zhang, Bo; Zhao, Shuting; Wan, Hao; Liu, Ying; Zhang, Fei; Guo, Xin; Zeng, Wenqi; Zhang, Haiyan; Zeng, Linghua; Qu, Jiale; Wu, Ben-Qing; Wan, Xinhong; et al.
Abstract : Correction for 'High-resolution DNA size enrichment using a magnetic nano-platform and application in non-invasive prenatal testing' by Bo Zhang et al., Analyst, 2020, 145, 5733–5739, DOI: ; 10.1039/D0AN00813C .